Antisense imaging of colon cancer-bearing nude mice with liposome-entrapped 99m-technetium-labeled antisense oligonucleotides of c-myc mRNA - Zheng, Jian-Guo (World J Gastroenterol, 2004)
AIM: To investigate the feasibility for antisense imaging of the colon cancer with liposome-entrapped 99 m-technetium labeled antisense oligonucleotides as tracers. METHODS: Fifteen mer single-stranded aminolinked phosphorothioate antisense oligonucleotides of c-myc mRNA were labeled with (99m)Tc-pertechnetate, then purified and finally entrapped with liposomes to form the labeling compounds, liposome-entrapped (99m)Tc-labeled antisense oligonucleotides. The LS-174-T cells (colon of adenocarcinoma cell line) were incubated with the labeling compounds to test the uptake rates of LS-174-T cells. Later on, a model of 30 tumor bearing nude mice was constructed by inoculating with 5 × 10(6) of LS-174-T cells at right flank of each nude mouse. About 10 d later, the model were adminstered by intravenous injection of the liposome-entrapped (99m)Tc-labeled antisense oligonucleotides. Then some of the tumour bearing nude mice were sacrificed at 0.5, 1, 2, and 4 h after intravenous injection, and proper quantity of liver, spleen, tumor, etc. was obtained. The tissues were counted in a gamma counter, and after correction for decay and background activity, expressed as a percentage of the injected dose. The others whose anterior and posterior whole-body scans were obtained at 1, 1.5, 2, 4, 6 and 24 h with a dual-head bodyscan camera equipped with parallel-hole low-energy collimaters. The ratios of radioactive counts in tumor to that in contralateral equivalent region of abdomen were calculated. RESULTS: The uptake rates of LS-174-T cells for liposome-entrapped (99m)Tc-labeled antisense oligonucleotides increased as time prolonged and reach the peak (17.77% ± 2.41%) at 7 h. The biodistributions showed that the rdioactivity in the tumor (13.46% ± 0.20%) of injected dose was the highest at 2 h of intravenous injection of liposome-entrapped (99m)Tc-labeled antisense oligonucleotides, and then decreased sharply to 4.58% ± 0.45% at 4 h. The tumor was shown clearly in the whole-body scan at 2 h of intravenous injection. The ratios, radioactive counts in tumor to that in contralateral equivalent region of abdomen (1.7332 ± 0.2537), was the highest one at 2 h after intravenous injection of liposome-entrapped (99m)Tc-labeled antisense oligonucleotides. CONCLUSION: The liposome-entrapped (99m)Tc-labeled antisense oligonucleotides deserve being developed into radiopharmaceutics for the colon cancer imaging.